2014
DOI: 10.1073/pnas.1320715111
|View full text |Cite
|
Sign up to set email alerts
|

Seminal vesicle protein SVS2 is required for sperm survival in the uterus

Abstract: In mammals, sperm migrate through the female reproductive tract to reach the egg; however, our understanding of this journey is highly limited. To shed light on this process, we focused on defining the functions of seminal vesicle secretion 2 (SVS2). SVS2 −/− male mice produced sperm but were severely subfertile, and formation of a copulatory plug to cover the female genital opening did not occur. Surprisingly, even when artificial insemination was performed with silicon as a substitute for the plug, sperm fer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
110
1
3

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 107 publications
(121 citation statements)
references
References 44 publications
3
110
1
3
Order By: Relevance
“…Plug survival was not correlated with either PC1 or PC2 (F 1, 6 = 4.25, 1.55; P = 0.09, 0.26, respectively). Variation in Svs2 did not seem to explain variation in plug mass, and this is surprising given its importance in plug formation (Kawano et al, 2014).…”
Section: Proteomic Analysesmentioning
confidence: 81%
See 1 more Smart Citation
“…Plug survival was not correlated with either PC1 or PC2 (F 1, 6 = 4.25, 1.55; P = 0.09, 0.26, respectively). Variation in Svs2 did not seem to explain variation in plug mass, and this is surprising given its importance in plug formation (Kawano et al, 2014).…”
Section: Proteomic Analysesmentioning
confidence: 81%
“…The full exomes will be published as part of a larger study elsewhere, but we focus here on these five genes as they are either necessary for copulatory plug formation or present in seminal vesicles and plugs at high abundance (Lundwall et al, 1997;Dean et al, , 2011Dean, 2013;Kawano et al, 2014). DNA was sheared using a Bioruptor UCD-200 (Diagenode, Denville, NJ, USA) with 7 rounds of sonication (7 min per round on high, 30 s on and 30 s off) and genomic DNA libraries were constructed using a previously described protocol designed to facilitate multiplexed exome capture (Rohland and Reich, 2012).…”
Section: Exome Sequencingmentioning
confidence: 99%
“…After copulation, SVS2 enters the uterus and attaches to the sperm head in order to protect sperm (Kawano & Yoshida 2007, Kawano et al 2014, Araki et al 2015. To examine whether this is also true for SVS3 and SVS4, we measured SVS3 and SVS4 quantities in each part of the female reproductive tract we collected, 1.5 h after copulation: the copulatory plug, the vagina, the uterine region near the vagina, the uterine region near the oviduct and the oviduct.…”
Section: Resultsmentioning
confidence: 99%
“…Although decapacitation by various factors has been reported (Dukelow et al 1966, Davis 1974, Reyes et al 1975, Huang et al 1999, Lu et al 2011, Tseng et al 2013, their in vivo functions remain unclear. On the other hand, the seminal vesicle plays an important role in sperm fertility, and the removal of seminal vesicles from mice results in the decline of fertility (Pang et al 1979, Bromfield et al 2014, Kawano et al 2014. Previously, we reported that seminal vesicle secretory protein 2 (SVS2), which is one of the secreted proteins from the seminal vesicle (SVSs), has two effects on sperm capacitation: an inhibitory effect on initiation of capacitation (capacitation inhibitor role) and cancellation of fertility of the capacitated spermatozoa (decapacitation factor role) (Kawano & Yoshida 2007.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation